2011
DOI: 10.1093/humrep/der010
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal activation of Ras/Raf/MAPK and RhoA/ROCKII signalling pathways in eutopic endometrial stromal cells of patients with endometriosis

Abstract: BACKGROUND Enhanced proliferation and survival of eutopic endometrial cells from patients with endometriosis compared with healthy women is associated with abnormal activation of extra-cellular signal-regulated kinases 1 and 2 (ERK1/2). Given the role of Ras/Raf/mitogen-activated protein kinase (MAPK) and RhoA/ROCKII signalling pathways in the regulation of cell proliferation and migration, we analysed their possible roles in endometriosis. METHODS Primary eutopic endometrial stromal cells of patients with end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 52 publications
4
79
1
3
Order By: Relevance
“…In addition, Rac2 regulates actin cytoskeletal machinery during the formation of lamellipodia and membrane ruffles, cell migration and adhesion of immune cells (GomezCambronero, 2011). Abnormal activation of Rho GTPases is implicated in diseases, such as tumorigenesis (Aznar and Lacal, 2001;Benitah et al, 2003;Karlsson et al, 2009), endometriosis (Yotova et al, 2011) and Fragile X syndrome (Chen et al, 2010). Hence, activation of Rho GTPases and the upstream guaninenucleotide exchange factors (GEFs) is tightly regulated (Pai et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Rac2 regulates actin cytoskeletal machinery during the formation of lamellipodia and membrane ruffles, cell migration and adhesion of immune cells (GomezCambronero, 2011). Abnormal activation of Rho GTPases is implicated in diseases, such as tumorigenesis (Aznar and Lacal, 2001;Benitah et al, 2003;Karlsson et al, 2009), endometriosis (Yotova et al, 2011) and Fragile X syndrome (Chen et al, 2010). Hence, activation of Rho GTPases and the upstream guaninenucleotide exchange factors (GEFs) is tightly regulated (Pai et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These MAPK signaling pathways are also present in endometrial cells, and MAPKs play pathophysiological roles in the development of endometriosis (14,27). It has been shown that MAPK signaling pathways are abnormally activated in HESCs, and that MAPK acts upon the regulation of HESC proliferation (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…45 More recently, in an attempt to understand the molecular mechanisms that control not only the baseline proliferation of endometrial human cells but also their migration, it was demonstrated for the first time that the protein rho-associated kinase II (ROCKII) acts as a point of integration between cell proliferation and migration, and that the protein Rapidly accelerated fibrosarcoma-1 (Raf-1) regulates negatively the activity of ROCKII in endometrial cells. 46 Still, since levels of Raf-1 are lower and B-Raf activity is higher in eutopic endometrial cells than in normal cells, the B-Raf-MAPK and Rho/ROCKII pathways are abnormally activated, leading to a greater proliferation ability and increased migratory potential, which explains the incomplete transition in the damaged endometrium and the high proliferative migratory phenotype (Figure 1e*).…”
Section: Non-genomic Signaling In Endometriosismentioning
confidence: 99%
“…7 One of the main features of the eutopic endometrium in patients with endometriosis has been the incomplete transition of the proliferative (estrogen-dependent) to the secretory (progesterone-dependent) endometrium, leading to a persistent expression of genes involved in the synthesis of DNA and cellular mitosis in endometriotic lesions. 8,9 In addition, latest research shows that the proliferative phase is not a uniform period of endometrial growth. 10 This represents without any doubt a great challenge in the search for the understanding of the mechanisms of cellular signaling by which estrogen regulates the human endometrium.…”
Section: Introductionmentioning
confidence: 99%